Frequency and gender differences in the use of professional home care in late life. Findings from three German old-age cohorts - Buczak-Stec, Elżbieta W.; Hajek, André; Pabst, Alexander; Brettschneider, Christian; van den Bussche, Hendrik; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Hoell, Andreas; Pentzek, Michael; Fuchs, Angela; Luppa, Melanie; et al. (Frontiers in Medicine, 2022)
Aim The aim of this study was to investigate the frequency of and the gender differences in the use of professional home care in Germany. Methods We used harmonized data from three large cohort studies from Germany (“Healthy Aging: Gender-specific trajectories into the latest life”; AgeDifferent.de Platform). Data were available for 5,393 older individuals (75 years and older). Mean age was 80.2 years (SD: 4.1 years), 66.6% were female. Professional homecare outcome variables were use of outpatient nursing care, paid household assistance, and meals on wheels' services. Logistic regression models were used, adjusting for important sociodemographic variables. Results Altogether 5.2% of older individuals used outpatient nursing care (6.2% women and 3.2% men; p < 0.001), 24.2% used paid household assistance (26.1% women and 20.5% men; p < 0.001) and 4.4% used meals on wheels' services (4.5% women and 4.0% men; p = 0.49). Regression analysis revealed that women had higher odds of using paid household assistance than men (OR = 1.48, 95% CI: [1.24–1.76]; p < 0.001), whereas they had lower odds of using meals on wheels' services (OR = 0.64, 95% CI: [0.42–0.97]; p < 0.05). No statistically significant differences in using outpatient nursing care between women and men were found (OR = 1.26, 95% CI: [0.87–1.81]; p = 0.225). Further, the use of home care was mainly associated with health-related variables (e.g., stroke, Parkinson's disease) and walking impairments. Conclusions Our study showed that gender differences exist in using paid household assistance and in culinary dependency. For example, meals on wheels' services are of great importance (e.g., for individuals living alone or for individuals with low social support). Gender differences were not identified regarding outpatient nursing care. Use of professional home care services may contribute to maintaining autonomy and independence in old age.